Gaze interaction and applications of eye tracking advances in assistive technologies - Majaranta, Paivi, 1967- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
"This book focuses on interactive communication and control tools based on gaze tracking, including eye typing, computer control, and gaming, with special attention to assistive technologies"--